Safe, mild ultraviolet‐B exposure: An essential human requirement for vitamin D and other vital bodily parameter adequacy: A review. Issue 6 (9th August 2020) - Hawk, J.L.M.
Abstract: The enigma of skin sunburning, skin ageing and skin cancer and essential vitamin D production both resulting from solar ultraviolet‐B (280‐315 nm) (UVB) exposure has long puzzled photobiologists. Advice to patients by non‐photobiological clinicians is now often to sunbathe to acquire vitamin D adequacy. However, modern work shows only mild UVB exposure is needed to maintain satisfactory levels, which have been demonstrated as very similar in summer and winter from about 25° to 70° north. Even very careful high protection factor 15 sunscreen use does not prevent adequate production, although it is slightly reduced, such that obsessive use of very protective screens of 50 + might. Dark skin pigmentation too usually at most minimally impairs production. However, confinement indoors and widespread clothing cover can, but oral supplementation overcomes any such deficiency. Thus, vitamin D adequacy needs just mild regular UVB skin exposure well under sunburning levels, unlikely to cause significant skin damage. This suggests mild UVB exposure may also be needed for other bodily requirements, which is indeed so. Thus, it also prevents the development of contact dermatitis and polymorphic light eruption through suppressing adaptive immunity. It also prevents the occurrence of multiple skin infections resulting from this suppression through stimulating innate immunity and cutaneous bacterial defensin production. Finally, blood pressure is reduced through low‐dose UVB‐induced production of the vasodilator nitric oxide (though UVA, 315‐400 nm, is more efficient). Thus, mild UVB exposure is important for several aspects of internal health, whereas high‐dose exposure is extremely detrimental to cutaneous health.